Answer:
x = -9
Explanation:
multiply 2 on both sides which cancels out the 2 in the fraction and then do -1 times 2 and 2 times x (which is just 2x). After doing that your equation should look like 3x + 7 = 2x - 2
Collect your like terms (the numbers with an x variable go togther and the ones with an x have to be together) and rearrange it so it looks like: 3x - 2x = -2 - 7 after you have this written subtract 3 from 2 now because they're on the same side which leaves you with x (usually we leave out the one because it doesn't make a difference) so now you're left with x = -2 - 7 for this step subract -2 from 7 which leaves you with x = -9
Steps:
3x + 7 = 2x - 2
3x - 2x = -2 -7
x = -2 - 7
x = -9